Force degradation trend of latex and nonlatex orthodontic elastics after 48 hours stretching - I Gusti Aju Wahju Ardani (2018)
Background: Two types of orthodontic elastics exist based on their material, latex and nonlatex, each of which has different properties in clinical use. Some of the differences include their initial force and force degradation over time. This study was conducted to compare the force changes in both materials. Aim: To evaluate the force degradation of latex and nonlatex elastics under moderate stretching over time. Methods: Medium-force orthodontic latex and nonlatex elastics from American Orthodontics(AO) and Ortho Technology (OT) of lumen size 1/4 inches and 3/16 inches (total sample 110 elastics) were submerged in artificial saliva (pH 6.7) and incubated for 48 hours. Then, the elastic force was measured at the following time intervals: initial, 1, 3, 6, 12, 24, and 48 hours. Orthodontic latex and nonlatex elastics from AO and OT were analyzed using Fourier-Transform Infrared Spectroscopy and energy-dispersive X-ray to know the chemical bond structure and elements. Results: There was a statistically significant difference between latex and nonlatex force degradation over a period of 0–24 hours (P<0.05), while no significant difference existed between 24–48 hours (P>0.05). Force degradation of latex elastics was higher than that of nonlatex elastics. Energy-dispersive X-ray results on nonlatex elastic bands from OT and AO showed higher C element in the latex elastic band from OT, while the latex elastic band from AO had higher Al element. Conclusion: Medium-force latex and nonlatex elastics 1/4 inches and 3/16 inches in size both showed force degradation at 1, 3, 6, 12, and 24-hour intervals under 30 mm stretching when kept in artificial saliva (pH 6.7) and incubated at 37°C for 48 hours.